2017
DOI: 10.1371/journal.pone.0169689
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Possibility of Cryopreservation of Feline and Canine Erythrocytes by Rapid Freezing with Penetrating and Non-Penetrating Cryoprotectants

Abstract: Efficient application of veterinary blood transfusion approaches for small companion animals requires readily available supply of the donor material. This can be achieved by developing of effective biobanking technologies allowing long-term storage of donor blood components via cryopreservation. Transfusion of an erythrocyte concentrate allows the successful correction of various hematological pathologies, severe bleeding, and etc. While in the past there were several approaches to cryopreserve red blood cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…[6][7][8][9][10][11][12] Canine cryopreservation techniques have also been successfully described in three previous reports using modifications of both automated and manual human protocols. [19][20][21][22] However, our findings are consistent with a recent study 23 that evaluated glycerol and HES as cryoprotectants for both canine and feline pRBCs. This study reported that neither HES nor glycerol were able to cryopreserve and recover feline RBCs successfully.…”
Section: Discussionsupporting
confidence: 90%
“…[6][7][8][9][10][11][12] Canine cryopreservation techniques have also been successfully described in three previous reports using modifications of both automated and manual human protocols. [19][20][21][22] However, our findings are consistent with a recent study 23 that evaluated glycerol and HES as cryoprotectants for both canine and feline pRBCs. This study reported that neither HES nor glycerol were able to cryopreserve and recover feline RBCs successfully.…”
Section: Discussionsupporting
confidence: 90%
“…Cryopreservation with 10% DMSO showed statistically similar survival compared to cryopreservation with 5% DMSO (data not shown). The lower concentration was selected for the further experiments since it is generally preferred to reduce the DMSO concentration in cryopreservation media due to cytotoxicity [ 31 , 32 , 33 , 34 , 35 , 36 , 56 ]. Importantly, it was observed, that even the native (non-cryopreserved) cells harvested from the MK differentiation cultures had no more than 74.25% ± 6.95% of viable cells.…”
Section: Resultsmentioning
confidence: 99%
“…Among the obligatory requirements to clinically relevant biobanking the key role belongs to the compatibility with good manufacturing practice and good laboratory practice standards, which assumes application of serum- and xeno-free protocols throughout the process. Besides, serious clinical safety concerns are currently being associated with the use of DMSO during cryopreservation [ 31 , 32 , 33 , 34 , 35 , 36 ]. Therefore, these issues were particularly addressed as the core of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the cryopreservation of erythrocytes of domestic mammals however, the development of new techniques is still required. For example, the standard cryoprotectants for human erythrocytes, based on glycerol or 1.2-propanediol (1,2-PD) (3,4), are found to be ineffective for erythrocytes of many animals (5,6). Compared to glycerol and __________________________ *Correspondence to: Olena M. Bobrova, Institute for Problems of Cryobiology and Cryomedicine of the National Academy of Sciences of Ukraine, Department of Cryobiophysics, 23 Pereyaslavskaya str., 61016 Kharkiv, Ukraine; е-mail: helen.bobrova.77@gmail.com 1,2-PD, dimethyl sulfoxide (DMSO) provides better results in the cryopreservation of equine, bovine, feline and canine erythrocytes, however, the level of hemolysis after all stages of cryopreservation is still quite high (5,6).…”
Section: Introductionmentioning
confidence: 99%